(untitled) (American Journal of Pedagogical and Educational Research, 2022)
The cultural values of the people and their spiritual heritage have served as a powerful source of spirituality for the peoples of the East for thousands of years. Despite the harsh ideological pressure for a long period, the people of Uzbekistan managed to preserve their historical and cultural values and original traditions, which were carefully passed down from generation to generation.